The Relationship Between Stress Coping Strategies and Work-Life Balance Among Bank Employees - Rezky Ariany Aras; Tandiayuk Suryadi; Rezky Nurul Fatihah (Universitas Negeri Makassar, 2023)
Several studies showed that bank employees face high job demands, which impact their work-life balance. Exceeding standard working hours and encountering significant stressors require employees to employ coping strategies to support their performance and daily lives. Therefore, the objective of this study is to determine the relationship between stress coping strategies and work-life balance, as well as the role of problem-focused and emotion-focused coping strategies on work-life balance among bank employees. This research involved 141 bank employees in Makassar City, South Sulawesi. The results revealed that both coping stress strategies have a positive correlation (r=0.417, p<0.001). Among the coping strategies, problem-focused coping had a greater impact.